Validation of the portuguese version of the tampa scale for kinesiophobia heart (TSK-SV HEART) Validação da versão em português da escala de tampa para cinesiofobia cardíaca (TSK-SV cardíACA) Validación de la versión en portugués de la escala de tampa para kinesiofobia cardiaca (TSK-SV CARDIACA) - Ghisi G.L.D.M. (2017)
© 2017, Redprint Editora Ltda. All rights reserved.Introduction: It has been shown that kinesiophobia has a negative influence on the outcomes of cardiac rehabilitation and consequently is important for the clinical setting. Objective: The objective of this study was to translate, culturally adapt, and psychometrically validate the Tampa Scale for Kinesiophobia Heart (TSK-SV Heart) to Brazilian Portuguese. Methods: The Portuguese version was tested in 300 patients in cardiac rehabilitation. Test-retest reliability was assessed by intraclass correlation coefficient, internal consistency by Cronbach’s alpha, and criterion validity was assessed with respect to patients’ education, income, duration of cardiac rehabilitation, and sex. Results: After intraclass correlation coefficient analysis, one item was excluded. All four areas were considered internally consistent (α >0.7). Significant differences between mean total scores and income (p<0.01) supported the criterion validity. Two hundred sixty-nine (89.6%) patients had a high level of kinesiophobia (scores > 37). Conclusions: The Brazilian Portuguese version of TSK-SV Heart demonstrated sufficient reliability, consistency and validity, supporting its use in future studies.